Clinical implication of ectopic liver lipid accumulation in renal cell carcinoma patients without visceral obesity. Issue 1 (December 2017) - Watanabe, Daisuke; Horiguchi, Akio; Tasaki, Shinsuke; Kuroda, Kenji; Sato, Akinori; Asakuma, Junichi; Ito, Keiichi; Asano, Tomohiko; Shinmoto, Hiroshi
Abstract Fatty liver has emerged as a prognostic marker of cancer, so we investigated the impact of ectopic lipid accumulation in liver on the clinical outcome for patients with renal cell carcinoma (RCC). The records of 230 consecutive patients who had undergone surgery for RCC were reviewed, and liver lipid accumulation was estimated from the attenuation in unenhanced preoperative CT images. The median liver CT values of patients with G3 tumors was lower than that of patients with G1–2 tumors (P  = 0.0116), that of patients with pT3–4 tumors was lower than that of patients with pT1–2 tumors (P  = 0.0336), and that of patients with visceral obesity defined as a visceral fat area ≥ 100 cm2 was lower than that of patients without visceral obesity (P  < 0.0001). In patients without visceral obesity the median liver CT values of patients with pT3–4 tumors was lower than that of patients with pT1–2 tumors (P  = 0.0401), that of patients with metastasis was lower than that of patients without metastasis (P  = 0.026), and fatty liver was associated with shorter overall survival (P  = 0.0009). Ectopic lipid accumulation in liver thus seems to be a predictor of aggressive forms of RCC.